IMPLEMENTASI KEBIJAKAN DALAM MENINGKATKAN EFEKTIVITAS PENANGGULANGAN SAMPAH DI PASAR TATAAN KABUPATEN PESAWARAN - Achmad Suharyo; Esha Erlangga (e-JKPP, 2022)
This study mainly wants to know and clarify matters concerning the implementation of policies in increasing the effectiveness of waste management in the Tataan Market, Pesawaran Regency. The purpose of this research is to obtain explanatory knowledge to identify and analyze the implementation of policies in increasing the effectiveness of waste management in the Tataan Market, Pesawaran Regency.The research method used in this research is using qualitative research with descriptive analysis method. The use of this method is to examine and describe qualitatively, how to implement policies in increasing the effectiveness of waste management in the Pesawaran District Management Market.The results showed that the implementation of policies in increasing the effectiveness of waste management at the Tataan Market, Pesawaran Regency, was not optimal because according to the results of the study that the facilities (vehicles, carts, TPS) used were minimal and then there was no Landfills  available in the long or medium term. This is in accordance with the results of the study showing that from the dimensions used, namely communication, disposition, quality of resources, and bureaucratic structure, all of these dimensions are still not optimally implemented.